Development of plasticized PLA/NH2‐CNTs nanocomposite: potential of NH2‐CNTs to improve electroactive shape memory properties. Issue 11 (15th January 2014) - Alam, Javed; Alam, Manawwer; Arockiasamy Dass, Lawrence; Shanmugharaj, A. M.; Raja, Mohan
<x xml:space="preserve">Abstract</x> A polymer nanocomposite system comprising epoxidized soya oil plasticized‐polylactic acid (PLA) and amine functionalized carbon nanotubes (NH2 functionalized‐CNTs) has been prepared with the aim of producing electrically conductive PLA products suitable for shape memory (SM) applications. An influence of the addition of NH2 functionalized‐CNTs on thermal, mechanical properties, and morphology development of plasticized PLA/NH2 functionalized‐CNTs nanocomposite was investigated by differential scanning calorimetry, tensile tests, scanning electron microscope, and atomic force microscopy, respectively. In addition, electroactive SM behavior in resulting nanocomposite was evaluated by a bending test, and the recovery process was recorded with video camera. The results showed that SM behavior in nanocomposite was influenced by NH2 functionalized‐CNTs weight percent in matrix. Nanocomposite with 5 wt% NH2 functionalized‐CNTs showed optimum values of shape recovery due to its relatively high electrical conductivity, and an adequate degree of crosslinking between NH2 functionalized‐CNTs and plasticized PLA matrix. However, more than 5 wt% loading of NH2 functionalized‐CNTs dropped down an elongation at break, while tensile at break increased with the increasing of CNTs weight percent in matrix. Interesting point in this study is that all improvements in the properties of resulting PLA/NH2 functionalized‐CNTs nanocomposite sheet were observed at very low filler content, while other literature reports where large quantities of CNTs were used. POLYM. COMPOS., 35:2129–2136, 2014. © 2014 Society of Plastics Engineers